Mechanism of Impurity Content in Degradation and Damage Characteristics of Calcium Fluoride Crystals by X-Ray and Deep-Ultraviolet Laser Irradiation - Ping Han; Dapeng Jiang; Huamin Kou; Rongrong Liu; Qinghui Wu; Zhonghan Zhang; Zhen Zhang; Chong Shan; Chongyun Shao; Yafei Lian; Yuanan Zhao; Xing Peng; et al. (Photonics)
Calcium fluoride (CaF2) crystals are widely utilized in deep-ultraviolet (DUV) lithography due to their excellent optical properties. The laser-induced degradation and damage of CaF2 crystals is a critical concern that restricts its extended application. Impurities of CaF2 crystal are considered a key factor affecting its laser resistance. Establishing the quantitative relationship and mechanism of impurity content impacting the degradation and damage characteristics of CaF2 crystal is essential. This study investigated the characteristics of different impurity contents affecting the degradation and laser-induced damage thresholds (LIDTs) of CaF2 crystals under X-ray and 193 nm pulsed laser irradiations, and quantitatively analyzed the degradation process and mechanism. Our findings demonstrate that impurities at ppm levels significantly diminish the transmittance of CaF2 crystals across various wavelengths following X-ray irradiation. In contrast, these impurities have a negligible effect on the LIDT test results, suggesting distinct damage mechanisms between X-ray and laser irradiation. This study provides valuable insights for optimizing the CaF2 crystal fabrication process and enhancing irradiation resistance.